Case report: Suspected plasmablastic lymphoma in a dog resembling the clinical presentation in humans - Giuliano, Antonio; Lam, Sin Yan; Flecher, Mayra C.; Horta, Rodrigo S. (Frontiers in Veterinary Science, 2023)
Plasmablastic lymphoma (PBL) is a rare form of lymphoma in people. PBL originates from plasmablasts and usually presents with swelling/mass in the mouth/neck. A 7-year-old Mongrel dog was presented for a large oral and neck mass. Cytology and histopathology were suggestive of a round cell tumor that was suspected to be lymphoma. An immunohistochemical (IHC) stain panel showed positive for CD18, thus supporting the diagnosis of round cell tumor, but negative for T- and B-cell lymphomas, CD3, CD20, and PAX-5. Other markers including cytokeratin AE1/3 (for epithelial cell origin), CD31 (for endothelial cells), SOX10 (for melanoma), IBa-1 (for histiocytic sarcoma), and CD117 (for mast cell tumor) were all negative. MUM-1 (for plasma cell differentiation) was strongly positive and CD79a (B cell and plasma cells) was also scantly positive. Based on the histopathology and immunohistochemistry results in combination with the clinical presentation, a suspected diagnosis of PBL was made. As per available literature, this is perhaps the first highly suspected case of PBL in a dog.